The Association Between Bullying Victimization and Fighting in School Among US High School Students - Chacon, Marco (Journal of interpersonal violence, 2022)
In-school fighting often results in severe punishment and compromised learning outcomes, without adequate consideration of contextual factors or student vulnerabilities. In this study, using a large, nationally representative data sample from the 2019 Youth Risk Behavior Survey (N = 13677), we assessed associations between a history of bullying victimization (at school and online) and past year fighting at school among U.S. high school students. Multiple regression models were used, adjusting first for demographics, and then for demographics and emotional-behavioral risks (depressive symptoms, alcohol consumption, and sexual violence victimization), for the total sample and then stratified by gender/sex. Both cyberbullying and in-school bullying were significantly associated with past year in-school fighting for the total sample, with associations retained, but marginally attenuated in fully adjusted models (cyberbullying: AOR: 1.30; 95% CI: 1.01?1.66 and in-school bullying: AOR: 1.96, 95% CI: 1.57?2.45). Gender/sex-stratified models demonstrated retained associations for males (cyberbullying: AOR: 1.93; 1.51?2.46 and in-school bullying: AOR: 2.70, 95% CI: 2.18?3.34) and females (cyberbullying: AOR: 1.89; 1.33?2.68 and in-school bullying: AOR: 1.66, 95% CI: 1.19?2.33) after adjusting for demographics, but only for males after adjusting for demographics and emotional-behavior risk factors (cyberbullying: AOR: 1.43; 95% CI: 1.07?1.93 and in-school bullying: AOR: 2.25; 95% CI: 1.73?2.92). These results demonstrate a significant association between bullying victimization and fighting, which was amplified for male students, and partially explained by social and emotional risks. This suggests that punitive approaches to fighting in school may be resulting in compounded harms for already vulnerable adolescents and that support-oriented approaches emphasizing conflict resolution, social-emotional well-being, positive gender identity development, and bullying prevention may be more appropriate.